The Effect of Institutional Ownership on Financial Performance With Intellectual Capital as A Moderating Variable - Retnawati Siregar; Nadiya Yunan; Rudy Irwansyah; Deri Apriadi; Made Susilawati (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Researchers believe that Institutional Ownership can have a positive relationship and a significant influence on a company's Financial Performance because more and more companies, government institutions, and so on as external parties owning shares in a company can increase the value of the company and ultimately have a good impact on Financial Performance. Therefore, this research aims to analyze the influence of institutional ownership on financial performance. Different from a number of previous studies, this research adds the Intellectual Capital variable as a moderating variable. This research is quantitative research with an explanatory approach. The data used in this research is secondary data that researchers obtained from PT's financial reports. Gudang Garam is spread throughout Indonesia. These data were analyzed using the smart PLS 4.0 analysis tool. The result in this article show the Institutional Ownership variable has a positive relationship and a significant influence on the Financial Performance variable because the p-values are below the significance level of 0.042. Apart from that, the Intellectual Capital variable can moderate the influence of the Institutional Ownership variable because the P-Values are also below the 0.05 significance level, namely 0.005. Thus the first and second hypotheses in this research can be accepted.